Freshwater Animal Diversity Assessment - Balian, E.V; Lévêque, C.; Segers, H.; Martens, K. (Developments in Hydrobiology, 2008)
The Freshwater Animal Diversity Assessment gives a state of the art assessment of the diversity and distribution of Metazoa in the continental waters of the world. The project deals with all major animal groups plus the macrophytes, and encompasses the complete array of terrestrial aquatic ecosystems. It is the most comprehensive study of species- and genus-level diversity and chorology of the global freshwater fauna to date, and is the first to present comparable data on the different faunal groups concerned. The project draws from the collected expertise of numerous world-renowned taxonomic experts that have bundled efforts to produce this outstanding volume. The result is invaluable to all scientists, managers and conservationists interested in non-marine aquatic animals.